Sympathetic ophthalmia following corneal patch graft for corneal perforation: Poster Presentation - Case Report - Ophthalmologist - RENI ANGRAINI; Havriza Vitresia (Majalah Oftalmologi Indonesia, 2023)
Introduction : Sympathetic ophthalmia (SO) is a rare, bilateral, diffuse granulomatous uveitis that usually occurs after open globe injury or intraocular surgery. We report a rare case of SO after the closure of corneal perforation using a corneal patch graft. Case Illustration : A 12 year old boy diagnosed as corneal perforation in the right eye, with visual acuity (VA) 20/100, underwent a corneal patch graft. He presented with redness and decreased vision in both eyes 2 weeks after surgery. The patient had VA of hand movements in the RE and 20/200 in the LE. Anterior segment examination showed a corneal patch graft with iris adherent to the graft posteriorly in RE, endothelial dusting, 2+ cells in both eye. Fundus examination showed optic disc oedema in both eye and inferior retinal detachment with macular involvement in RE. The patient was managed with pulse steroids for three days followed by oral steroids in tapering doses along with continued topical steroids. Three months follow-up showed improvement of VA to 20/60 in RE and 20/25 in LE Discussion : SO is thought to be an autoimmune response to uveal injury. The incarceration of uveal tissue in the wound is a major risk factor. SO has been reported 5 days to 66 years after penetrating insult to the eye. In this case, incarceration of uvea in corneal pacth resulted in SO 2 weeks after surgery. Conclusion : In a case of a perforated cornea, the possibility of iris incarceration in the wound is high and hence SO can develop